Crystal structure and EPR studies of doped Cu2+ ion in [Zn(sac)2(en)2] single crystal - Karabulut, Buenyamin; Ucar, Ibrahim; Koksal, Fevzi; Yerli, Yusuf (Pergamon-Elsevier Science Ltd, 2010)
The tran-bis(ethylenediamine)bis(saccharinato)Zinc(II), (Zn(sac)(2)(en)(2)] (ZSED), (en: ethylenediamine and sac: saccharinate) complex has been synthesized and its crystal structure has been determined by X-ray diffraction analysis. The compound crystallizes in space group P2(1)/c. The Zn(II) ion is hexa-coordinated by four nitrogens of two bidentate en ligands composing the basal plane and two nitrogen atoms from the monodentate two sac ligands (N-bonded) occuping the axial sites, adopting an elongated octahedral sphere. Both en and sac ligands occupy the trans positions of the coordination octahedron. The Zn(II) ion in title compound sits on a inversion centre and is octahedrally coordinated two bidentate en (ethylenediamine) and two sac (saccharinate) (N-bonded) ligands. The magnetic environments of Cu2+ doped [Zn(sac)(2)(en)(2)] complex have been identified by electron paramagnetic resonance (EPR) technique. Cu2+ doped ZSED single crystals have been studied at room temperature in three mutually perpendicular planes. The calculated results of the Cu2+ doped ZSED indicate that Cu2+ ion contains two magnetically inequivalent Cu2+ sites in distinct orientations occupying substitutional positions in the host lattice and show very high angular dependence. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: X-ray diffraction; Crystal structure; Electron paramagnetic resonance (EPR); Magnetic properties